2022
DOI: 10.1002/asl.1138
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Aeolus horizontal Line‐Of‐Sight (HLOS) wind assimilation on the Korean integrated model (KIM) forecast system

Abstract: The Korean Integrated Model (KIM) forecast system, based on a hybrid fourdimensional ensemble-variational method, was extended to assimilate Horizontal Line-Of-Sight (HLOS) wind observations from the Atmospheric Laser Doppler Instrument (ALADIN) on board the Atmospheric Dynamic Mission Aeolus satellite. In a global cycling experiment, assimilation of Aeolus HLOS wind observations led to reductions in the average root-mean-square error of 0.8 and 0.5% for the zonal and meridional wind analyses when compared aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This is in contrast to the results of George et al (2021), who mostly saw the smallest impact in the Northern Hemisphere when assimilating from May 20 to June 22, 2020. Studies by Lee et al (2022) and Garrett et al (2022), where Aeolus was assimilated in a period during Northern Hemisphere summer, found the strongest impacts occurred in the Southern Hemisphere and Tropics. Wind observations often have the greatest impact in the winter hemisphere, where the jets are stronger, which may account for this difference.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This is in contrast to the results of George et al (2021), who mostly saw the smallest impact in the Northern Hemisphere when assimilating from May 20 to June 22, 2020. Studies by Lee et al (2022) and Garrett et al (2022), where Aeolus was assimilated in a period during Northern Hemisphere summer, found the strongest impacts occurred in the Southern Hemisphere and Tropics. Wind observations often have the greatest impact in the winter hemisphere, where the jets are stronger, which may account for this difference.…”
Section: Discussionmentioning
confidence: 97%
“…Lee et al (2022) also saw improved analysis errors in the tropical upper troposphere mean zonal wind analysis. Garrett et al (2022) observed changes to the zonal mean zonal wind analysis in the Tropics but at higher altitude than Lee et al (2022) did. Garrett et al (2022) used the National Oceanic and Atmospheric Administration (NOAA) FV3GFS model to assimilate Aeolus HLOS winds using four-dimensional ensemble-variational assimilation, from August 2 to September 16, 2019, a very similar period to Laroche and St-James (2022).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Despite the unforeseen signal loss and lower precision, Aeolus winds were assimilated into the ECWMF model through the four‐dimensional variational (4D‐Var) data assimilation technique to improve operational weather forecasts (Rennie et al., 2021). To assess the added value of Aeolus observations to NWP, many institutions have conducted Observing System Experiments (OSEs) with global NWP models, including ECMWF, National Oceanic and Atmospheric Administration (NOAA), Deutscher Wetterdienst (DWD), Météo‐France, Environment and Climate Change Canada, Korean Integrated Model (KIM), etc (Borne et al., 2023; Garrett et al., 2022; Laroche & St‐James, 2022; Lee et al., 2023; Pourret et al., 2022; Rennie et al., 2021). The evaluations demonstrated that with Aeolus data assimilation, the wind vector forecasts are improved by up to 4%, particularly in the upper troposphere and/or lower stratosphere over the tropics and polar regions (Garrett et al., 2022; Laroche & St‐James, 2022; Pourret et al., 2022; Rennie et al., 2021).…”
Section: Introductionmentioning
confidence: 99%